The Significance of Education Programmes for Dynamic Entrepreneurship in Maximizing Regional Competitiveness - Ćorić, Gordana; Senegovic, Iva; Bekic, Ivana (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
.